Time changes with feeling of speed: an embodied perspective - Zhang, Zhijie; Jia, Lina; Ren, Weicong (Frontiers in Neurorobotics, 2014)
The present study aimed to investigate whether the words describing different speeds can influence the subjective duration. Duration estimation of different speed words (fast-speed vs. slow-speed words in Chinese characters) were compared in temporal bisection task. We found that time bisection point (TBP) was significantly lower for fast-speed words than for slow-speed words, and the just noticeable differences (JND) were not significantly different between these two types of words. These results suggest that the durations of fast-speed words were overestimated compared with the slow-speed words and provide evidence to support the theory of embodied cognition in the context of implicit meaning of a speed word.